Biobutanol Production Using Fed-Batch High-Cell Density Extractive Fermentation - Rizki Fitria Darmayanti; Yukihiro Tashiro; Kenji Sakai; Kenji Sonomoto (Journal of Biobased Chemicals, 2020)
Butanol, as a product with specific toxicity for its producer, is necessary to be maintained in low concentration during fermentation. In-situ integrated recovery using extensive volume extraction was used in high cell density fermentation in order to prevent the lag phase in the prime condition. Clostridium saccharoperbutylacetonicum N1-4 ATCC 13564 was employed to ferment glucose in extractive fermentation with oleyl alcohol as extractant. As the results of fed-batch cultures using high cell density with different extractant to broth volume ratios (Ve/Vb), 0.8 g/l butanol concentration in the broth was maintained with a ratio of 10, which was much lower than 4.4 g/l with the ratio of 0.5. Besides, the Ve/Vb ratio of 10 demonstrated 2.7-fold higher total butanol concentration (28 g/l) than that 11 g/l obtained with a Ve/Vb ratio of 0.5. These results indicated that larger Ve/Vb improved total butanol concentration by reducing butanol toxicity in broth.